Thesaurus based automatic keyphrase indexing - Medelyan, Olena; Witten, Ian H. (International Conference on Digital Libraries: Proceedings of the 6th ACM/IEEE-CS joint conference on Digital libraries; 11-15 June 2006, 2006)
We propose a new method that enhances automatic keyphrase extraction by using semantic information on terms and phrases gleaned from a domain-specific thesaurus. We evaluate the results against keyphrase sets assigned by a state-of-the-art keyphrase extraction system and those assigned by six professional indexers.